Effect of calcination temperature on the morphological and dielectric properties of phase-pure MnCrFeO4 nanoparticles. Issue 12 (2nd December 2017) - Akhtar, Khalida; Gul, Muhammad; Haq, Ikram Ul; Shah, S. Sajjad Ali; Khan, Zia Ullah
ABSTRACT: Phase-pure MnCrFeO4 particles were synthesized by the controlled precipitation and the effect of calcination on different properties were investigated. XRD results showed intermediate phases in the particles calcined at 800 °C, while complete transformation into spinel phase at 1000 °C. The particle size increased linearly with calcination temperature. The increase in AC conductance with frequency showed the involvement of small polarons in the conduction mechanism. The dielectric constant and loss tangent steeply decreased while remained constant over the high frequency range. The phase-pure MnCrFeO4 particles showed lowest dielectric losses that make them a promising candidate for application in high-frequency devices.